Enhanced Acetone, Butanol, and Ethanol Fermentation by Clostridium saccharoperbutylacetonicum N1-4 (ATCC 13564) in a Chemically Defined Medium: Effect of Iron and Initial pH on ABE Ratio - HANIES AMBARSARI AMBARSARI; KENJI SONOMOTO (Indonesian Society for microbiology, 2012)
Batch studies were performed to investigate the performance of Clostridium saccharoperbutylacetonicum N1-4 (ATCC 13564) in acetone-butanol-ethanol (ABE) fermentation as affected by iron and initial pH in defined TYA (Tryptone-Yeast extract-Acetate) media. Different concentrations of FeSO4.7H2O in the TYA media were found to influence the ABE fermentation process resulting in different ABE ratios. From the experiment with different concentrations of FeSO4.7H2O, it was also found that lag phases at initial pH of 4.4 were longer than those at initial pH of 6.5, however they could still have higher ABE productivity values. Addition of 0.003 g L-1 FeSO4.7H2O could give the highest ABE production with both initial pH of 6.5 and 4.4. With more than 0.01 g L-1 FeSO4.7H2O, ratios of acetone to butanol (0.50 - 0.53) were higher at initial pH of 4.4 than those (0.26 - 0.28) at initial pH of 6.5. Those differences were not obtained with low concentration of FeSO4.7H2O among the same initial pH. It was also confirmed that initial pH affected ABE production significantly more than FeSO4.7H2O by statistical analysis.